Moderate alterations of the cytoskeleton in human chondrocytes after short‐term microgravity produced by parabolic flight maneuvers could be prevented by up‐regulation of BMP‐2 and SOX‐9. Issue 6 (13th February 2015) - Aleshcheva, Ganna; Wehland, Markus; Sahana, Jayashree; Bauer, Johann; Corydon, Thomas J.; Hemmersbach, Ruth; Frett, Timo; Egli, Marcel; Infanger, Manfred; Grosse, Jirka; Grimm, Daniela
ABSTRACT: Real and simulated microgravity induce a variety of changes in human cells. Most importantly, changes in the cytoskeleton have been noted, and studies on microtubules have shown that they are gravisensitive. This study focuses on the effects of short‐term real microgravity on gene expression, protein content, and cytoskeletal structure of human chondrocytes. We cultivated human chondrocytes, took them along a parabolic flight during the 24th Deutsches Zentrum für Luft‐ und Raumfahrt Parabolic (DLR) Flight Campaign, and fixed them after the 1st and the 31st parabola. Immunofluorescence microscopy revealed no changes after the 1st parabola, but disruptions of β‐tubulin, vimentin, and cytokeratin networks after the 31st parabola. No F‐actin stress fibers were detected even after 31 parabolas. Furthermore, mRNA and protein quantifications after the 31st parabola showed a clear up‐regulation of cytoskeletal genes and proteins. The mRNAs were significantly up‐regulated as follows: TUBB, 2‐fold; VIM, 1.3‐fold; KRT8, 1.8‐fold; ACTB, 1.9‐fold; ICAM1, 4.8‐fold; OPN, 7‐fold; ITGA10, 1.5‐fold; ITGB1, 1.2‐fold; TGFB1, 1.5‐fold; CAV1, 2.6‐fold; SOX9, 1.7‐fold; BMP‐2, 5.3‐fold. However, SOX5 (‐25%) and SOX6 (‐28%) gene expression was decreased. Contrary, no significant changes in gene expression levels were observed during vibration and hypergravity experiments. These data suggest that short‐term microgravity affects the gene expression of distinct proteins. In contrast to poorly differentiated follicular thyroid cancer cells or human endothelial cells, chondrocytes only exert moderate cytoskeletal alterations. The up‐regulation of BMP‐2, TGF‐β1, and SOX9 in chondrocytes may play a key role in preventing cytoskeletal alterations.—Aleshcheva, G., Wehland, M., Sahana, J., Bauer, J., Corydon, T. J., Hemmersbach, R., Frett, T., Egli, M., Infanger, M., Grosse, J., Grimm, D. Moderate alterations of the cytoskeleton in human chondrocytes after short‐term microgravity produced by parabolic flight maneuvers could be prevented by up‐regulation of BMP‐2 and SOX‐9. FASEB J. 29, 2303‐2314 (2015). www.fasebj.org